The Robinson-Patman Act: federal regulation of price differences - Posner, Richard A. (Washington D.C. American Enterprise Institute for Public Policy Research, 1976)
The book examines the statute enacted forty years ago to curb anticompetitive price discrimination. The author concludes that the act serves no function that could not be better performed in its absence, and indeed that has never been more than a non-solution to the problems it supposedly addresses
osc 28/01/2019
Loans
Keywords: Price Discrimination; Robinson-Patman Act; United States of America